Epicatechin, procyanidins, and phenolic microbial metabolites after cocoa intake in humans and rats - Urpi-Sarda, Mireia; Monagas, Maria; Khan, Nasiruddin; Lamuela-Raventos, Rosa M; Santos-Buelga, Celestino; Sacanella, Emilio; Castell, Margarida; Permanyer, Joan; Andres-Lacueva, Cristina (Analytical and bioanalytical chemistry, 2009)
Proanthocyanidins, flavonoids exhibiting cardiovascular protection, constitute a major fraction of the flavonoid ingested in the human diet. Although they are poorly absorbed, they are metabolized by the intestinal microbiota into various phenolic acids. An analytical method, based on an optimized 96-well plate solid-phase extraction (SPE) procedure and liquid chromatography tandem mass spectrometry (SPE-LC-MS/MS) for the analysis of 19 phenolic microbial metabolites and monomeric and dimeric flavanols in urine samples, was developed and validated. Human urine samples were obtained before and after ingestion of an acute consumption of 40 g of soluble cocoa powder and rat urines before and after the prolonged administration (2 weeks) of different diets composed of natural cocoa powder. The mean recovery of analytes using the new SPE-LC-MS/MS method ranged from 87% to 109%. Accuracy ranged from 87.5% to 113.8%, and precision met acceptance criteria (<15% relative standard deviation). Procyanidin B2 has been detected and quantified for the first time in human and rat urine after cocoa consumption. Changes in human and rat urinary levels of microbial phenolic acids and flavanols were in the range of 0.001-59.43 nmol/mg creatinine and of 0.004-181.56 nmol/mg creatinine, respectively. Major advantages of the method developed include reduction of laboratory work in the sample preparation step by the use of 96-well SPE plates and the sensitive measurement of a large number of metabolites in a very short run time, which makes it ideal for use in epidemiological studies.